Market power risk prevention mechanism of China’s electricity spot market based on stochastic evolutionary game dynamics - Xie, Jingdong; Guan, Bowen; Yao, Yin; Li, Ruizhen; Shi, Quan (Frontiers in Energy Research, 2023)
The construction of China’s power spot market is still in its early stage, with a high concentration on generation-side resources and frequent market power. It is urgent to establish risk prevention mechanisms for the generation of market power. First, the paper establishes a basic framework of the stochastic evolutionary game theory and then builds a “stochastic evolutionary game market-clearing” model for the market regulator and risk units. Second, the work provides a library of multi-dimensional monitoring and evaluation indicators for the regulator and creates a quantitative risk prevention strategy for the power spot market in China. Finally, an evolutionary dynamic analysis is conducted on players’ strategic evolution space and changes in market risks. Based on a simulation of actual data from an electricity market in China, it turns out that the generation-side market power risk prevention mechanism can lower market transaction and operational risks in a variety of power supply–demand scenarios. The study theoretically supports the development of market power risk prevention and provides more realistic insights into China’s power spot market as well.